1997
DOI: 10.1039/a702724i
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the benzylic bond dissociation enthalpy in benzyl bromides (C–Br) and tert-butylbenzenes (C–CH3): a gas phase thermolysis and liquid phase photoacoustic study

Abstract: The bond dissociation enthalpies in a number of substituted benzyl bromides have been studied in the gas phase, using the toluene carrier technique, and in solution with photoacoustic calorimetry. Gas phase thermolysis with unsubstituted benzyl bromide gives an absolute C᎐Br bond dissociation enthalpy (E d ) at 298 K of 255 ± 4 kJ mol ؊1 . Competition experiments in the gas phase reveal no substituent effect on the value of E d (C᎐Br). Gas phase thermolysis with substituted tert-butylbenzenes also shows no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
24
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…Thus, our results are more consistent with those of Leigh et al 10 and Laarhoven et al 9 (i.e., no significant substituent effects on C-Br BDEs) than with the results of Clark and Wayner 11 or Andrieux et al 12 (i.e., substantial effects, see the introduction). We therefore The trends in the calculated enthalpies for isodesmic reaction 4 (∆H 4 ) should correspond to the trends in the calculated enthalpies for isodesmic reaction 2 (and 3), i.e., to ∆∆BDE-(X-H).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, our results are more consistent with those of Leigh et al 10 and Laarhoven et al 9 (i.e., no significant substituent effects on C-Br BDEs) than with the results of Clark and Wayner 11 or Andrieux et al 12 (i.e., substantial effects, see the introduction). We therefore The trends in the calculated enthalpies for isodesmic reaction 4 (∆H 4 ) should correspond to the trends in the calculated enthalpies for isodesmic reaction 2 (and 3), i.e., to ∆∆BDE-(X-H).…”
Section: Discussionsupporting
confidence: 89%
“…We have found no published data on the energy of the SCl bond in arenesulfonyl chlorides. Fu et al [11] analyzed the effect of remote substituent Y in the aromatic ring on the energy of dissociation of the XZ bond in YC 6 H 4 XZ molecules (RMP2/6-311++G**//UB3LYP/6-31G*) and found that substituent in the aromatic ring only slightly affects the energy of the CH and CF bonds in compounds YC 6 H 4 CH 2 Z where Z = H, F, which is well consistent with the experimental data [9]. However, the substituent effect on the energy of dissociation of the XZ bond in YC 6 H 4 SZ and YC 6 H 4 NHZ (Z = H, F) turned out to be fairly strong.…”
supporting
confidence: 81%
“…In addition, substituents can change the energy of the initial state due to dipoledipole interaction with the CBr bond. However, the recent experimental data on the energy of dissociation of the CBr bond in benzyl bromides showed that it almost does not depend on the substituent within experimental error (1 kcal/mol) [9]; therefore, the effect of substituent on the stability of benzyl radical via delocalization of the unpaired electron, as well as on the energy of the initial state via dipole dipole interaction, is negligible.…”
mentioning
confidence: 98%
“…) are formed, the contrasting variation in the bond dissociation enthalpies must be due to a ͑de͒stabilization of the parent The results by Clark and Wayner mentioned above 95 have been recently questioned by Mulder and co-workers, 96 who found no change in C-Br bond dissociation enthalpies in several para-substituted benzyl bromides. We believe, however, that the dipole interaction hypothesis remains a useful reasoning, although it is not entirely clear, after the above discussion on stability, what authors mean by ''stabilization of the compound.''…”
mentioning
confidence: 94%